Valuing pollination services in the apple orchards of Kashmir valley - K Mahendar; F A Shaheen; Fehim J Wani; S A Wani; M A Parray; Haseeb Rehman; S A Saraf; S A Mir (Agricultural Economics Research Review, 2023)
In the Kashmir valley, managed pollination orchards yield 35.22 tons per hectare of apples on average, 19.43% more than the non-managed orchards’ yield of 29.49 tons, and the quality of fruit is also better. Pollination services improved the income of managed apple orchards, and its value for apple in the Kashmir valley is estimated at INR 126.56 billion per annum. If managed pollination services are extended to the entire area under the apple crop, an additional pollination welfare implication to the tune of INR 29.71 billion (almost INR 300 crore) will be realized per annum.